Socio-economic status of the farmers and economic analysis of poultry farming at Gazipur district in Bangladesh (International Journal of Natural Sciences, 2016)
The study was conducted to identify the socio-economic status of the poultry farmers and economic analysis of poultry farming at Gazipur, Bangladesh. A Total of 40 poultry farms (20 broilers and 20 layers) were selected. The farmers and farming were evaluated through the analysis of data that were collected in a pre-structured questionnaire. This study revealed that comparatively rich farmers (42.5% had >4.94 acre of land) were involved in farming. There were significant variations (p0.05) in farm size and management skills of the farmers. The average number of children per farmer attends to primary school, high school, college and university were 0.7, 0.75, 0.1 and 0.01 in case of boys and 0.5, 0.45, 0.07 and 0.01 in case of girls, respectively. Per bird average annual rearing cost, return, and cost benefit ratio were 925.5 BDT., 1080 BDT. and 1:1.17 in broiler and 1332.5 BDT., 2210 BDT. and 1:1.66 in layer, respectively. This study recommends although initial investment is higher; layer farming is more profitable than broiler.International Journal of Natural Sciences (2014), 4(2) 8-12